Private Equity Fund Structures in Czech Republic within the Framework of the New Institutional Economics - Martina Skalicka; Marek Zinecker; Tomas Meluzin (Institute of Economic Research (IER), 2017)
Institutional aspects of a well-functioning private equity and venture capital market are emphasized in the recent academic literature. In particular, a favourable tax and legal environment is essential, since formal institutions enable the industry to attract a larger volume of investors and thus to contribute more efficiently to the growth of GDP. In the Czech Republic, however, legal barriers represent an essential obstacle affecting a rather poor scope of resources available to domestic private equity and venture capital funds.This paper examines the current tax and legal environment for private equity and venture capital investments in the Czech/ Republic. Proposals for prospective improvements of legal and tax framework are made in the empirical part of the study.As the phenomenon under study is complex and explanatory in nature, qualitative data with content analysis proved to be the best way how to assess institutional framework for PE/VC in the Czech Republic. Data collection methods cover a comparative analysis of scientific literature documents and reports, as well as primary data from interviews with experts in the industry. The results of both secondary and primary data analysis were categorized and core lacks in the institutional framework were identified and discussed. Finally, proposals for prospective improvements of the institutional framework are made. The conducted analysis implies that the issue of the legal and organisational structure suitable for PE/VC funds may be deemed resolved in the Czech Republic. A Czech equivalent to a Limited Partnership (SICAR), i.e. a limited partnership with investment certificates, has already with provided with sufficient support in the legislation in terms of the legal form. The legal form is a necessary, yet not sufficient condition. A tax handicap was identified implying that it is necessary to amend the tax law so that the legal regulation extends the tax exemption. Another amendment to the applicable legislation should then be directed towards eliminating or mitigating the barriers imposed on pension funds when investing in PE/VC funds.
Keywords: B25; G24; K23; 330; new institutional economics; private equity; venture capital; tax and legal environment; private equity fund structures